Preparation of novel UV-curable methacrylated urethane resins from a modified epoxy resin and isocyanatoethylmethacrylate (IEM) - (:unkn) unknown (SPRINGER-VERLAG, 2002)
New UV curable methacrylated urethanes (PAPHEN-XIEM) were synthesized by substituting X percent (e.g., 10, 20, 30 %) of the total OH content of the PAPHEN-301 (Scheme 1) with isocyanatoethyl methacrylate (IEM). These resins were used alone (neat resin formulation) or as a mixture of 5, 10 and 13 % (w/w) respectively with methacrylated urethane prepolymer (PTHFUMA) in UV systems. For neat resin formulations, tensile strength and modulus values were observed to be inversely proportional with the modification degree of PAPHEN-301 as opposed to what is normally expected. This may be explained as a result of screening effect of increasing unsaturation. The water absorption capacities for neat resins and PTHFUMA-included formulations were decreased as the modification degree increased due to the replacement of hydrophilic OH groups of PAPHEN-301 by the hydrophobic methacrylate groups. TGA thermograms of neat resin formulation show that, initial weight loss temperatures are lower; possibly owing to the higher methacrylate content in the formulations.